Foetal haemoglobin concentration at postmenstrual age is unaffected by gestational age at birth. (May 2018) - Watanabe, Yuki; Osawa, Kayo; Sato, Itsuko; Iwatani, Sota; Kono, Ruri; Hayakawa, Ikuyo; Hayashi, Nobuhide; Iijima, Kazumoto; Saegusa, Jun; Morioka, Ichiro
Background: Our aim was to determine whether the postnatal age or postmenstrual age is a more appropriate criterion for evaluating foetal haemoglobin concentrations. Methods: Blood samples ( n  = 1095) were obtained from 394 infants and were divided into two groups based on gestational age at birth: <37 weeks ( n  = 491) and ≥37 weeks ( n  = 604). (1) Foetal haemoglobin concentrations divided by one month at age after birth were compared between the groups. (2) Foetal haemoglobin concentrations divided into ≤9 months from last menstruation and one month thereafter were compared between the groups. Results: In samples from infants ≥37 weeks' gestational age at birth, the median foetal haemoglobin concentrations were 69.5%, 21.4% and 3.6% at 0–1 month, 2–3 months and ≥5 months after birth, respectively. The median foetal haemoglobin concentrations in infants <37 weeks' gestational age at birth were 75.5%, 62.7% and 5.1% at 0–1 month, 2–3 months and ≥5 months after birth, respectively. The median foetal haemoglobin concentrations in infants <37 weeks' gestational age at birth were significantly higher than that in infants ≥37 weeks' gestational age at birth at all postnatal age points. (2) There was no significant difference between the groups at all age points after nine months of postmenstrual age: 72.5 and 75.3% at 9–10 months, 25.1 and 26.6% at 11–12 months and 5.5 and 4.6% at >13 months after last menstruation in infants ≥37 and <37 weeks' gestational age at birth, respectively. Conclusions: Evaluation of foetal haemoglobin concentrations at postmenstrual age is unaffected by gestational age at birth.